A parallel approach to performance and sport psychology work in esports teams - Watson, M.; Abbott, C.; Pedraza-Ramirez, I. (International Journal of Esports, 2021)
Prompted by the paucity of existing literature on best-practice approaches to applied sport psychology in esports, this perspective paper proposes a parallel approach involving separate roles for a sport psychologist and a performance coach on the same esports team. We briefly outline a number of key practical and ethical considerations that underpin this approach as well as applied sport psychology work in esports more generally.